An acoustic and auditory analysis of vocants in infants with cochlear implants - Binos, Paris; Thodi, Chryssoula D.; Vogazianos, Paris; Psillas, George K.; Constantinidis, Jiannis (My University, 2021)
Introduction: The duration of the nuclei is a crucial factor for the shift of prelexical to mature speech, since control of duration is closely related with improved speech intelligibility. Objectives: This work records the suprasegmental feature of duration in infants with normal hearing (NH) compared to those with cochlear implants (CI) based on vocant productions (quasivowels and full vowels). Materinals and Methods: In this longitudinal study, 102 vocant productions were analyzed from cases of congenitally hearing-impaired infants (implantation ages 1:4 and 1:11 years; post-implant ages 0:6 months and 1:3 years) who were matched with three NH infants of similar hearing experience (ages 0:8–0:11 months). Current methodology analyzes vocants using a combination of acoustical and auditory analyses. Vegetative data or reflexive sounds were excluded. Participants had had unknown deafness etiology and no other disabilities. Duration was measured using wideband spectrographic analysis, from voice onset to the loss of audible signal and the decrease of higher formant’s energy. Results: The results showed that the mean vocant duration of young CI users was longer, compared to hearing matched peers during the first six months after cochlear implantation. Conclusions: This recorded weakness for CI users' speech production is a challenge for future work in speech processing strategies. This is the first study measuring production of vocants during the pre-linguistic stage in CI recipients.
Keywords: Cochlear implants; Duration; Quasivowels; Spectrogram; Speech production; Suprasegmental features; Vocant